PENGARUH PRETREATMENT BAHAN KIMA DAN BIOLOGI TERHADAP AKUMULASI VOLUME BIOGAS DARI LIMBAH MAKANAN - Adi Permadi; Totok Eka Suharto (Agroindustrial Technology Journal, 2023)
In daily activities can produce garbage commonly called household waste. Food waste is included in household waste that has an impact on the environment. Household food waste has the potential to release methane gas into the environment causing damage to the earth's ozone layer because it includes greenhouse gases that can cause climate change. The increasing impact of food waste requires serious efforts to deal with the processing of household food waste. One of the efforts to overcome this is to mix household waste with cow dung to make biogas. In addition, it is also an effort to reduce fossil energy sources with renewable energy sources from biogas. This study aims to knowing the influence of chemical pretreatment (Ethanol, NaoH, and HCl) and Biology (EM-4 enzyme) at concentrations of 8%, 10% and 12% on the accumulation of biogas from food waste (rice and vegetables) produced for 30 days. While the pre-treatment results using chemicals (ethanol, HCl and NaOH) and biological materials (EM-4 enzymes) at concentrations of 8%, 10% and 12% provide a larger volume of biogas accumulation for 30 days, compared to raw materials. biogas that does not get pre-treatment. From this study, the pretreatment of biogas raw materials using 10% NaOH provided the highest accumulation of biogas volume (70 ml) in 30 days compared to other pretreatments.